Epidemiologic comparative burn analysis in LUHS Hospital Kaunas Clinics during 2003–2005 vs. 2013–2015 - Grigaitė, Augustina; Rainys, Domantas; Pilipaitytė, Loreta; Rimdeika, Rytis (Lietuvos chirurgija, 2017)
Background and objectives Burns are one of the most severe traumas, which traumatism has been changing over the past decades, globally and nationally. In LUHS hospital Kaunas Clinics, a study which analyses latest tendencies in burn epidemiology has not been conducted. Since 1972 LUHS Hospital Burns Center has been a national severe burns treatment center, thus our study data well represents national burns statistics. Our study aim was to analyze and compare data about burned patients who were admitted to Plastic and Reconstructive Surgery and Burns Department in LUHS Hospital Kaunas Clinics during two periods: 2003–2005 and 2013–2015. Methods This was a retrospective study. Patients from two comparison groups: treated in 2003–2005 and during 2013–2015 were divided according to age, gender, burn etiology, depth, degree, localization, hospitalization stay, surgery time (early surgery 7 days post-burn). Overall data from 757 burn patients admitted during both periods were collected and analyzed. Results Statistically significantly more men suffered from burn injuries during the both periods (66.3% men, 33,7 % women). A statistically significant correlation between burn mechanism and gender was found: men are more likely to be burned by flame, women by scald. The most common burn localizations were arm, legs and head/neck/face regions. During the second period statistically significantly less arm, stomach/waist and leg region burns occurred. Flame was the most common burn cause in both periods. Hospital stay during the second period was statistically significantly shorter (26 days vs. 24 days). Deep burn number statistically significantly decreased from 79.5% to 49.3%. When comparing burn surgery tactics more early burn necrectomies (135 vs. 165) were performed sooner after the trauma (10 vs. 8 days) in 2013–2015. Conclusions Our study results match worldwide burns epidemiologic and treatment tendencies: less deep burns occur (79.5% during first period, 49.3% during the second period, p
Keywords: burns; trauma; epidemiology